Dinamika penyelenggaraan pendidikan keagamaan Islam Etnis Tionghoa Muslim di Kota Padangsidimpuan - Asfiati Asfiati (Indonesian Institute for Counseling, Education and Therapy (IICET), 2019)
This study aims to determine the condition of ethnic Chinese Muslims in organizing Islamic religious education in the city of Padangsidimpuan. The Muslim Chinese community participated in moving Islamic religious education in the city of Padangsidimpuan The research method uses qualitative. Instrument for collecting data on observation, interview and documentation. The research findings show that the implementation of Islamic religious education developed in several centers of religious learning activities. The dynamics of the implementation of ethnic Muslim Islamic religious education in the city of Padangsidimpuan carried out in a variety of containers and facilities. The organization of religious education is based on groups and individuals.It was concluded that the Muslim Chinese ethnic studied religious learning material on aqeedah, sharia and morals. Learning methods build communication between educators and students. Educators and students come from various scientific backgrounds, Islamic and Indonesian.